Estudo do tema movimentos da Terra por meio de um compêndio de Astronomia Tropical e dispositivos educacionais correlatos - Athayde Junior, Luiz Sampaio (2025)
The seasons occur on planet Earth because of the tilt of its axis. In the tropical zone, the climatic patterns and the incidence of sunlight throughout the year make the differences between the seasons more subtle in this region, hindering their conceptualization. The differences are more evident outside the tropics, such as in European countries, which created rules and imposed them through northern literature on colonized countries. In Astronomy, zenith is the exact point above an observer, perfectly perpendicular to the ground where they are located. Locally, at the zenith of an observer in Feira de Santana, defined from the vertical line passing through the observer and appearing to "pierce" the sky at a point directly above their head, the Sun is at approximately October 26th, well before the official start of summer. Then, with rays at their zenith, it occurs again at approximately February 16th. For tropical locations, the seasons should not be defined with the same duration as in temperate zones, and the failure to observe this fact, as well as its absence in teaching and textbooks, can create dangers of sun exposure and an increase in diseases. Although this work deals with the seasons and the arrival of heat in tropical locations, meteorological factors will not be the subject of study in this text. The general objective of this work is to suggest the inclusion of concepts of Tropical Astronomy in education based on the reality of low-latitude regions, which are latitudes from 0º to approximately 20º on the equator. Thus, we could better guide the population in health care and also benefit from tourism by publicizing that the duration of summer is longer than what was conventionally established by Europeans centuries ago. Based on the observation of four associated elements, namely, the analemma, the orbit, the calendar, and the occurrence of the solar zenith in tropical latitudes, producing the analemma at subsolar points on the map, it is inferred that the planet varies its orbital speed twice a year, when passing through aphelion and perihelion. The solar day varies four times in its speed due to the apparent movement of the Sun, which always occurs from east to west. Thus, the variations in the speed of the apparent movement of the Sun occur on three occasions in an inverted manner in relation to the regime of variation of the planet's orbital speed, and on three other occasions they occur in concordantly with this same regime. A contribution to Keplerian harmony is evidenced by the harmonic velocities of each planet, which are linked to the inclination of its axis, regardless of its mass, distance from the Sun, whether it is rocky or gaseous, its diameter, or its orbital speed. One of the educational products related to this dissertation consists of the following experiments: 01 - Technical gnomon; 02 - A Fibonacci arc; 03 - An orb-shaped device installed at the Antares/UEFS Astronomical Observatory; 04 - A globe with copper wires to demonstrate the apparent helical motion of the Sun; and 05 - A model of the orbital solid. Another educational product, called "Compendium of Tropical Astronomy," comprises the theory involved in the 5 experiments mentioned.